Molecular aspects of Enterococcus faecalis virulence - Nur Asmah (Dentistry Faculty, 2020)
The Enterococcus faecalis (E. Faecalis) virulence factor plays an essential role in the persistence of root canal infection. Virulence factors of Enterococcus faecalis such as lipoteichoic acid, extracellular superoxide, gelatinase, hyaluronidase, and cytolysin are known to increase the ability of Enterococcus faecalis to induce inflammatory processes, colonization formation, and increase resistance. The virulence factor of E. faecalis is mediated by LTA, which has pattern recognition receptors for cytokine release, bone resorption and triggers apoptosis of osteoblasts, osteoclasts, periodontal connective tissue, macrophages, and neutrophils, which have implications for the occurrence of periradicular lesions. Lipoteichoic acid is also involved in producing D-alanine, which stimulates signals to other bacteria to form biofilms. The E. faecalis will change the balance of oxygen radical production in the periapical lesion, fragment collagen. The fight host's defense mechanisms that cause periapical damage and worsening bone loss. Furthermore, cytolysin will respond to changes in oxygen conditions in the depleting root canals for the dominance of E. faecalis against other bacteria. The energy needs of E. faecalis that assisted by hyaluronidase, which degrades hyaluronan dentin. t has to produce disaccharide degradation products that can be transported and metabolized intracellularly. These materials hydrolyzing the substrate to obtain essential carbon for its growth. This article aims to describe the molecular aspect of E. faecalis virulence that is involved in root canal infections.